2008
DOI: 10.1364/ao.47.000179
|View full text |Cite
|
Sign up to set email alerts
|

Speckle suppression in scanning laser display

Abstract: The theory of speckle noise in a scanning beam is presented. The general formulas for the calculation of speckle contrast, which apply to any scanning display, are obtained. It is shown that the main requirement for successful speckle suppression in a scanning display is a narrow autocorrelation peak and low sidelobe level in the autocorrelation function of the complex amplitude distribution across a scanning light beam. The simple formulas for speckle contrast for a beam with a narrow autocorrelation function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 5 publications
0
48
0
2
Order By: Relevance
“…The smallest ρ obtained was −0.431, and the corresponding C f was 0.535. In Equation (9), when the factor C 1 C 2 /C 2 avg < 1 for C 1 = C 2 , the sum pattern has a larger C f than the C f at C 1 = C 2 . This means that the lowest suppression result for a certain ρ occurs when the speckle contrasts of the two elementary patterns are equal.…”
Section: Suppression Factor Of the Sum Of Two Fully-developed Specklementioning
confidence: 99%
See 2 more Smart Citations
“…The smallest ρ obtained was −0.431, and the corresponding C f was 0.535. In Equation (9), when the factor C 1 C 2 /C 2 avg < 1 for C 1 = C 2 , the sum pattern has a larger C f than the C f at C 1 = C 2 . This means that the lowest suppression result for a certain ρ occurs when the speckle contrasts of the two elementary patterns are equal.…”
Section: Suppression Factor Of the Sum Of Two Fully-developed Specklementioning
confidence: 99%
“…Using DOEs in laser scanning displays, the scanning spot was split into several randomly-spread small spots [6], or modulated with phase arrays [7][8][9][10]. In systems projecting full-frame images, the DOE functioned as a changing diffuser to generate partially coherent illumination [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In articles, 7,8 it was shown that a static phase code with delta-like auto-correlation function can be effective in reducing laser speckle in line-scan laser projectors. A Barker binary phase code was chosen to demonstrate the method and a maximum speckle reduction with speckle contrast factor of 13% theoretical and 17% experimental value was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Small size and large optical efficiency are the main challenges in technology development of portable projection displays. Recently, the SOM device, the one-dimensional micro-actuation light modulator, is successfully developed by Samsung Electro-Mechanics for an accessory or embedded projection module [1][2][3][4][5][6][7][8][9][10]. But the previously developed SOM device, integrated in an optical module, has a volume bigger than 15 cc and entire module is considered to be too big in volume for being embedded in the mobile device.…”
Section: Introductionmentioning
confidence: 99%